Systematic Literature Review: Pengembangan Media Pembelajaran Menggunakan Model ASSURE - Syaiful Ulum Riswandi; Asep Wahyu Muhrom Dani; Yudha Prapantja; Zulfitria Zulfitria (Universitas Batanghari Jambi, 2026)
The development of information and communication technology has driven an increasing need for the development of learning media that is effective, adaptive, and capable of accommodating the characteristics and needs of learners. One widely used approach in technology-based learning media development is the ASSURE model, which emphasizes systematic instructional planning, analysis of learner characteristics, selection and utilization of media, active learner engagement, as well as evaluation and revision of instruction. This study aims to comprehensively examine the development of learning media using the ASSURE model through a Systematic Literature Review (SLR) approach. The SLR process was conducted following the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) by searching the literature in Google Scholar. The selection stages included identification, screening, and inclusion of articles based on specific criteria, resulting in 13 journal articles that met the eligibility requirements. Data analysis was conducted descriptively to systematically review the types of learning media developed, the research methods employed, and the effectiveness of the media in supporting student learning outcomes. The findings indicate that e-modules and videos are the most frequently produced types of learning media, while Research and Development (R&D) dominates the research methods used, accounting for 92% of the studies. Moreover, among all analyzed media, 54% have been tested for effectiveness and were proven effective in enhancing learning outcomes, motivation, and learner engagement. These results affirm that the ASSURE model has strong potential as a framework for designing systematic, learner-centered, and effective learning media.